2007
DOI: 10.2460/javma.231.2.227
|View full text |Cite
|
Sign up to set email alerts
|

A review of the causes, prevention, and welfare of nonambulatory cattle

Abstract: A major animal welfare issue facing the livestock industry is the care, handling, and transport of nonambulatory cattle. Consumers, researchers, practitioners, and animal protection organizations have questioned the quality of care provided to and management of nonambulatory cattle and raised questions about possible food safety concerns. Veterinarians and producers continue to be challenged with providing quality care for nonambulatory cattle. In addition, veterinarians are recognized as a credible source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
3
23
0
4
Order By: Relevance
“…As examples, badly fractured front legs and hind-limb tendon injuries were linked to shear grab accidents, fractured leg to slipping on slats, and neck muscle damage was attributed to a new gate system. White & Moore [33] and Stull et al [27] each mention that improved farm management, including care with farm machinery, would greatly reduce the incidence of ES/CS animals. Injuries involving other body systems were noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As examples, badly fractured front legs and hind-limb tendon injuries were linked to shear grab accidents, fractured leg to slipping on slats, and neck muscle damage was attributed to a new gate system. White & Moore [33] and Stull et al [27] each mention that improved farm management, including care with farm machinery, would greatly reduce the incidence of ES/CS animals. Injuries involving other body systems were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Stress during transport can result in latently infected animals shedding large numbers of pathogens [8]. Stull et al [27] found that E. coli 0157:H7 in faecal or tissue samples was 3.3 times greater among downer cows arriving at slaughterhouses compared to normal cattle (an incidence of 4.9% versus 1.5%, respectively). Transportation can also have a deleterious effect on product quality [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of nonambulatory animals based upon nonfed cattle reports from federally inspected plants during 1994 and 1999 were between 1.1% and 1.5% for nonambulatory dairy cows and 0.7% to 1.1% for nonambulatory beef cattle (Smith et al, 1994(Smith et al, , 1999Stull et al, 2007 ). During 2001, of 7382 nonambulatory fed and nonfed cattle arriving at 19 packing plants in Canada, 90% were dairy cattle (Doonan et al, 2003 ).…”
Section: Nonambulatory Cattlementioning
confidence: 99%
“…When an animal is on the ground, the shorter the period of the decubitus, the greater the chance is that it will be able to move again; the longer the decubitus, the more unfavorable the prognosis (Stull et al ., 2007). …”
Section: Introductionmentioning
confidence: 99%